Nefertiti resurrected [videorecording (DVD)] - Wortman, Matthew; Fletcher, Joann; Tunie, Tamara; Winslet, Kate (Artisan Home Entertainment, 2003)
Egyptologist Dr. Joann Fletcher investigates a hitherto unacknowledged side chamber of tomb K-V35. In this tomb, Dr. Fletcher and her associates come across the well-preserved remains of three "forgotten" mummies, surrounded by their worldly possessions. One of the mummified bodies is that of a woman, obviously of great importance to the Egyptian hierarchy. Can this be the body of the legendary Queen Nefertiti? Using state of the art DNA technology and educated speculation, Dr. Fletcher endeavors to find out if Nefertiti has indeed been rediscovered after all of these many centuries.